Experimental Investigation on Novel Parabolic Trough Collector - Lingaiah, G.; Sridhar, K. (Distributed Generation & Alternative Energy Journal, 2021)
With the increase in demand of the cleaner energy, the use of renewable sources of energy is increasing day by day and solar energy is the answer to it. Several methods are used to harness solar thermal energy among them Concentrating Parabolic Collectors (CPC) are widely used. In this paper, A novel CPC is made, and an experimental study is carried out to find out its efficiency in manual and automated single axis tracking mode using water as working fluid. It was observed that the automated tracking method outperforms the manual tracking method with efficiency reaching up to 48% as compared to 42% in the later. Methods to improve efficiency of the CPC are not used in this study. CPC was found suitable for domestic use.